A passenger's perspective of surface access issues at a UK regional airport: a case study of Robin Hood Airport Doncaster Sheffield. (2015) - Ryley, Tim J.; Zanni, Alberto M.
For environmental reasons, there is a need to reduce surface access journeys by private car, particularly 'drop-off/pick-up' trips, and to increase public transport usage. This paper examines surface access issues at the UK regional airport of Robin Hood Airport Doncaster Sheffield (RHADS), using data from an airport survey of 438 passengers. Most respondents were holiday makers travelling to-and-from RHADS by car, either via drop-off/pick-up or their own vehicle. There were five distinct passenger groups generated from cluster analysis of the attitudinal statements and the surface access mode chosen. Apart from the public transport supporters segment, the groups strongly favoured car-based surface access travel, particularly car-loving socialites and the practical drop-offs. A lack of willingness amongst passengers to change away from car travel and towards public transport for surface access journeys was identified, making it very difficult for airports to reduce the environmental impact of such trips.